2020
DOI: 10.1542/peds.2019-2689
|View full text |Cite
|
Sign up to set email alerts
|

Effect of State Immunization Information System Centralized Reminder and Recall on HPV Vaccination Rates

Abstract: BACKGROUND: Although autodialer centralized reminder and recall (C-R/R) from state immunization information systems (IISs) has been shown to raise childhood vaccination rates, its impact on human papillomavirus (HPV) vaccination rates is unclear. METHODS: In a 4-arm pragmatic randomized controlled trial across 2 states, we randomly selected practices representative of the specialty (pediatrics, family medicine, and health center) where children received care. Within each practice, patients 11 to 17.9 years old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Generally, series completion rates improved in the intervention group compared with the control group (Cates et al, 2018; Henrikson et al, 2018; McGaffey et al; Perkins et al, 2020; Zimmerman et al, 2017). Studies by McClean et al (2017) and Szilagyi et al (2015, 2020) did not demonstrate any improvement with the interventions implemented.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Generally, series completion rates improved in the intervention group compared with the control group (Cates et al, 2018; Henrikson et al, 2018; McGaffey et al; Perkins et al, 2020; Zimmerman et al, 2017). Studies by McClean et al (2017) and Szilagyi et al (2015, 2020) did not demonstrate any improvement with the interventions implemented.…”
Section: Resultsmentioning
confidence: 86%
“…Overall, vaccine series initiation rates improved in the intervention group compared with the control group (Bar‐Shain et al, 2015; Henrikson et al, 2018; McGaffey et al, 2018; Perkins et al, 2020; Rand et al, 2017; Zimmerman et al, 2017) ; however, McClean et al (2017) noted that children in the age group of 13–17 years were not significantly influenced by the intervention, while children in the age group of 11–12 years were significantly influenced. Szilagyi et al (2020) only reported improvement in initiation rates following a single phone call in Colorado practices, but otherwise did not report any improvements following intervention. Szilagyi et al (2015) was the only study that did not see any improvement with the interventions implemented.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations